Impact of disease duration and cardiovascular dysautonomia on hypertension in Parkinson's disease - Vetrano, Davide L. (J Clin Hypertens (Greenwich), 2016)
The authors evaluated the association of Parkinson’s disease (PD) duration with hypertension, assessed by office measurements and 24‐hour (ambulatory) monitoring, in 167 patients. Hypertension was evaluated through both office and ambulatory blood pressure (BP) measurements. Among participants (mean age 73.4±7.6 years; 35% women), the prevalence of hypertension was 60% and 69% according to office and ambulatory BP measurements, respectively (Cohen's k=0.61; P<.001). PD duration was inversely associated with hypertension as diagnosed by office measurements (odds ratio [OR], 0.92; 95% confidence interval [CI], 0.86–0.98) but not by ambulatory monitoring (OR, 0.94; 95% CI, 0.81–1.01). Ambulatory BP patterns showed higher nocturnal BP among patients with long‐lasting disease. In conclusion, ambulatory BP monitoring improves the detection of hypertension by 15% in PD, compared with office evaluation. The likelihood of having hypertension does not decrease during the PD course; rather, BP pattern shifts towards nocturnal hypertension.